تأثير ممارسات إدارة الأرباح كمتغير وسيط في العلاقة بين التطبيق الإلزامي لقواعد حوكمة البنوك ومصداقية القوائم المالية دراسة تطبيقية على البنوك التقليدية اليمنية - مسواك, حميد عبدالله علي (Journal of Amran University, 2024)
This study investigated the impact of profit management practices as an Intermediate variable in the relationship between the mandatory application of bank governance rules and the financial statement credibility in Yemeni traditional banks. The study was based on data obtained from the financial reports of Yemeni traditional banks published during the period from 2014 to 2018. The study yielded several key results: The level of disclosure of bank governance rules in the published financial reports of Yemeni traditional banks was low. There is an existence of earnings management practices in the financial reports of Yemeni traditional banks published during the period from 2014 to 2018. There is an positive relationship between the mandatory application of bank governance rules and the financial statements credibility in Yemeni traditional banks. There is an inverse relationship between the mandatory application of bank governance rules and earnings management practices in Yemeni traditional banks. There is an inverse relationship between earnings management practices and the credibility of financial statements in Yemeni traditional banks. The strongest overall impact on financial statements credibility was attributed to the variable of the mandatory application of bank governance rules.